Perioperative or neo/adjuvant chemoimmunotherapy versus chemotherapy for resectable non-small cell lung cancer: a systematic review and network meta-analysis - Qiong Zhang; Jia Duan; Yuanmei Zhang; Lei Yang; Duo Li (Systematic Reviews)
Abstract Introduction Lung cancer, particularly non-small cell lung cancer (NSCLC), is a leading cause of cancer-related deaths globally. Despite surgery being the main treatment for resectable NSCLC, many patients experience postoperative recurrence. Neoadjuvant chemotherapy may shrink tumors and improve surgical outcomes, while adjuvant chemotherapy targets residual disease post-surgery. Recent advancements in immunotherapy have introduced its use in the perioperative phase for resectable NSCLC. This study investigates the relative benefits and potential complications of neoadjuvant, adjuvant, and perioperative immunotherapy combined with chemotherapy compared to chemotherapy alone, focusing on event-free survival (EFS), overall survival (OS), and adverse events (AEs). Methods This systematic review and network meta-analysis followed PRISMA guidelines and was registered with PROSPERO. The authors searched PUBMED, Embase, and Cochrane databases for randomized controlled trials (RCTs) involving patients with resectable NSCLC treated with neoadjuvant/adjuvant immunotherapy or chemotherapy. Statistical analyses were performed using a frequentist network meta-analysis method in R software. Results From an initial 5902 articles, 13 RCTs involving 6704 patients were included after extensive filtering. PFS: Neoadjuvant and perioperative immunotherapy combined with chemotherapy showed significant benefits compared to chemotherapy alone. OS: Perioperative immunotherapy was notably more effective than adjuvant immunotherapy and standard chemotherapy. Chemotherapy generally had fewer severe adverse effects compared to neoadjuvant and perioperative immunotherapy. However, these immunotherapy combinations are generally well tolerated. Conclusions The findings indicate that neoadjuvant and perioperative immunotherapy combined with chemotherapy can significantly improve overall survival in patients with resectable NSCLC compared to standard chemotherapy. However, additional adverse effects associated with long-term immunotherapy require careful management. The lack of significant benefits in specific subgroups suggests a need for further research. The study stresses the importance of optimizing treatment strategies and potentially reassessing immunotherapy’s role in certain patient populations. Future clinical trials are anticipated to clarify these results further.